The toxic effects of subjective wellbeing and potential tonics. (November 2021) - Atkinson, Sarah
Abstract: The paper offers a provocation to the geographies of health in relation to one of our governing concepts, that of wellbeing. The paper brings together government survey data from the United Kingdom with other published research into a critical argument that the dominant ways of conceptualising and practising subjective wellbeing have become toxic and harmful to wellbeing outcomes. The paper argues that a 'hyper-individualised and thwarted self' and 'supermarket model' of social resources for individual wellbeing underpins the contemporary dominant understanding of subjective wellbeing. This approach neglects wider spatial and temporal considerations such as inequality, inter-generationality and sustainability, and the rise of wellbeing as a technology of soft capitalism. The paper discusses the potential for relational approaches from the social sciences to provide a more 'wholesome tonic' to current understandings of subjective wellbeing that might rehabilitate its capability to do helpful rather than harmful work and argues for an ethical obligation to sustain critical engagement. Highlights: The dominant understanding of subjective wellbeing creates negative consequences. Direct effects reduce wellbeing; indirect effects neglect importance issues. This dominant approach reflects and supports a political economy of soft capitalism. Centring the relational, social and interdependent fails to gain policy traction. Struggling to reframe subjective wellbeing is an ethical imperative.